Quantifying Through‐Space Substituent Effects. (17th July 2020) - Burns, Rebecca J.; Mati, Ioulia K.; Muchowska, Kamila B.; Adam, Catherine; Cockroft, Scott L.
Abstract: The description of substituents as electron donating or withdrawing leads to a perceived dominance of through‐bond influences. The situation is compounded by the challenge of separating through‐bond and through‐space contributions. Here, we probe the experimental significance of through‐space substituent effects in molecular interactions and reaction kinetics. Conformational equilibrium constants were transposed onto the Hammett substituent constant scale revealing dominant through‐space substituent effects that cannot be described in classic terms. For example, NO2 groups positioned over a biaryl bond exhibited similar influences as resonant electron donors. Meanwhile, the electro‐enhancing influence of OMe/OH groups could be switched off or inverted by conformational twisting. 267 conformational equilibrium constants measured across eleven solvents were found to be better predictors of reaction kinetics than calculated electrostatic potentials, suggesting utility in other contexts and for benchmarking theoretical solvation models. Abstract : The description of substituents as electron donating or withdrawing leads to a perceived dominance of through‐bond influences. The situation is compounded by the challenge of separating through‐bond and through‐space contributions. Measurements of through‐space substituent effects question classic descriptions of substituent effects.